2017
DOI: 10.1080/17549507.2017.1369567
|View full text |Cite
|
Sign up to set email alerts
|

The development and feasibility of an online aphasia group intervention and networking program – TeleGAIN

Abstract: TeleGAIN appeared to be feasible and acceptable, however the study highlighted issues related to technology, clinical implementation and participant-specific factors that should be addressed prior to a larger trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…A recent study in aphasia has demonstrated the feasibility of delivering online group therapy to people with aphasia living in their own homes (Pitt et al . ). In this study, multi‐point videoconferencing was used to connect to participants in their homes.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study in aphasia has demonstrated the feasibility of delivering online group therapy to people with aphasia living in their own homes (Pitt et al . ). In this study, multi‐point videoconferencing was used to connect to participants in their homes.…”
Section: Discussionmentioning
confidence: 97%
“…The therapy was delivered to groups of four participants using an Adobe Connect video conferencing platform. A pilot study and mixed methods phase 2 trial showed that TeleGAIN was feasible [35] and positively perceived by those who delivered the intervention [37]. Those who received TeleGAIN made significant improvements on a range of measures, including the Assessment of Living with Aphasia and the Comprehensive Aphasia Test [36].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence supports the feasibility of delivering traditional face-to-face therapy interventions via a telehealth platform (e.g., Hall et al, 2013;Pitt et al, 2018Pitt et al, , 2019). In the current study, a storytelling therapy delivered via the online platform, EVA Park, appeared to be feasible and resulted in improvements of direct measures of therapy including story content, story grammar, and argument structure.…”
Section: Discussionmentioning
confidence: 99%